2020
DOI: 10.3389/fpls.2020.00713
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Membranes and the Photosynthetic Apparatus to Salt Stress in Cyanobacteria

Abstract: Cyanobacteria are autotrophs whose photosynthetic process is similar to that of higher plants, although the photosynthetic apparatus is slightly different. They have been widely used for decades as model systems for studying the principles of photosynthesis, especially the effects of environmental stress on photosynthetic activities. Salt stress, which is the most common abiotic stress in nature, combines ionic and osmotic stresses. High cellular ion concentrations and osmotic stress can alter normal metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 115 publications
1
31
0
Order By: Relevance
“…A significant downregulation of the D1 protein gene was observed in Synechocystis sp. PCC 7338, which agrees with the previous results that the transcription and subsequent production D1 protein is inhibited by salt stress ( Figure 4B ; Allakhverdiev and Murata, 2008 ; Yang et al, 2020 ). As a result, the repair rate of damaged PSII would slow down, and oxidative stress would occur when excessive energy is transferred to PSII.…”
Section: Discussionsupporting
confidence: 93%
“…A significant downregulation of the D1 protein gene was observed in Synechocystis sp. PCC 7338, which agrees with the previous results that the transcription and subsequent production D1 protein is inhibited by salt stress ( Figure 4B ; Allakhverdiev and Murata, 2008 ; Yang et al, 2020 ). As a result, the repair rate of damaged PSII would slow down, and oxidative stress would occur when excessive energy is transferred to PSII.…”
Section: Discussionsupporting
confidence: 93%
“…Allakhverdiev et al [62] have realized that the augmentation of the polyunsaturated fatty acid in membrane lipids is able to conserve the plant's photosynthetic system. Other research has confirmed that abiotic stress such as saline stress leads to an increased proportion of unsaturated fatty acids [63]. In the biotechnology field, the study of the effect of these factors on seed oil quality gives an opportunity to develop tolerant safflowers genotypes having desirable fatty acid traits.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of salt in soil have become a primary abiotic stress that limits the productivity of processing tomatoes in Xinjiang Province (Pang et al, 2005). High salinity inhibits crop growth by disrupting a range of physiological processes involved in cell metabolism, especially photosynthesis (Thagela et al, 2017;Yang et al, 2020). Photosynthesis is the primary metabolic mechanism in plants (Singh et al, 2014) and is particularly sensitive to salinity (Ashraf and Harris, 2013).…”
Section: Introductionmentioning
confidence: 99%